THE ALCHEMY OF MYTH, HISTORY AND REALITY: A RE-READING OF SALMAN RUSHDIE’S MIDNIGHT’S CHILDREN - Kumar, Sooraj; S., Seema Rajan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
A flawless blend of myth and reality to narrate a versatile history of modern India through the lens of magical realism finds its fertile ground in Salman Rushdie’s Midnight Children. Through the life of the protagonist Saleem Sinai, whose birth coincides with the midnight hour of India’s independence, the novel investigates the interplay between personal identity and national history. Rushdie employs myth as a narrative strategy to critique the linearity of historical discourse, instilling historical events with a mythical dimension that challenges conventional notions of reality and truth. This article examines how the novel tries to reconstruct history through the lens of myth and memory, creating a space where the borders between the real and the imaginary are constantly unclear. The novel’s magical realist framework allows for reimagining historical events, transforming them into allegories of cultural and political significance. By interlacing individual experiences with the collective memory of a nation, Rushdie emphasizes the fragmented and multifaceted nature of identity in postcolonial India.